Financial literacy and its influence on financial decision: a bibliometric approach / Shuhaimi Samanol and Rosliza Md Zani - Samanol, Shuhaimi; Md Zani, Rosliza (Universiti Teknologi MARA, Perlis, 2024)
Financial literacy is critical in influencing financial decisions, particularly in today's complex financial market where individuals are constantly confronted with a diverse range of financial goods, complex investing possibilities, and ever-changing economic situations. The significance of making informed and wise financial decisions, including budgeting, savings, investments, and retirement planning, cannot be overstated. This prompts a gaining interest in financial literacy and its impact on financial decisions. More researchers are looking into various facets of financial literacy and how it affects individual's and society's financial well-being, subsequently paving the way for a better knowledge of this vital topic. Therefore, this study aims to highlight the current research trend on financial literacy influencing financial decisions. It involved a bibliometric analysis of data retrieved from the Scopus database by focusing on keywords related to financial literacy and financial decision-making. A total of 417 relevant documents were obtained for detailed analysis. Several analytical tools were used in this study, including Microsoft Excel for frequency analysis, VOSviewer for data visualization, and Harzing's Publish or Perish for citation metrics and analysis. The results were presented using typical bibliometric indicators, such as publication year, keyword analysis, geographical distribution, authorship, active institutions, and citation analysis. The findings showed a significant increase in financial literacy publications since 2014, highlighting the growing relevance of financial literacy and its broader societal impacts.